2014
DOI: 10.1016/j.bbadis.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondria in mutant SOD1 linked amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease with an adult onset characterized by loss of both upper and lower motor neurons. In ~10% of cases, patients developed ALS with an apparent genetic linkage (familial ALS or fALS). Approximately 20% of fALS displays mutations in the SOD1 gene encoding superoxide dismutase 1. There are many proposed cellular and molecular mechanisms among which, mitochondrial dysfunctions occur early, prior to symptoms occurrence. In this review, we modeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 118 publications
1
75
0
1
Order By: Relevance
“…PINK1, Parkin, and HtrA2 function in mitochondrial biogenesis and the autophagic degradation of mitochondria (mitophagy) (Desideri and Martins 2012). In ALS, SOD1 mutants induce mitochondrial dysregulation including disturbance of mitochondrial Ca 2+ flow (Tan et al 2014). The C9orf72 gene has been identified as the most frequently mutated gene in the familial forms of ALS and frontotemporal dementia (Mendez and Sattler 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PINK1, Parkin, and HtrA2 function in mitochondrial biogenesis and the autophagic degradation of mitochondria (mitophagy) (Desideri and Martins 2012). In ALS, SOD1 mutants induce mitochondrial dysregulation including disturbance of mitochondrial Ca 2+ flow (Tan et al 2014). The C9orf72 gene has been identified as the most frequently mutated gene in the familial forms of ALS and frontotemporal dementia (Mendez and Sattler 2014).…”
Section: Resultsmentioning
confidence: 99%
“…SOD1, the first identified ALS gene, has been extensively studied with regard to its role in the pathogenesis of this condition with the use of transgenic mice expressing various ALS-linked mutants of human SOD1 (Vinsant et al 2013). Such studies have revealed various mitochondrial abnormalities in these mice, including impairment of ATP permeation through the mitochondrial outer membrane, membrane hyperpolarization, and disturbance of mitochondrial Ca 2+ flow, which is functionally connected to Ca 2+ signaling in the endoplasmic reticulum (Tadic et al 2014;Tan et al 2014) (Fig. 2j).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Such observations have led to the hypothesis that mitochondrial dysfunction plays an important role in the pathogenesis of ALS, and a large number of studies in ALS patients and animal models have found mitochondrial abnormalities in neuronal and non-neuronal tissues [reviewed in [142]]. Furthermore, animal studies have revealed mitochondrial dysfunction in the pre-symptomatic and early phases of disease [143,144,145,146,147], implying that mitochondrial dysfunction is an early event that triggers disease rather than the end product of neuronal cell degeneration. Critically, mitochondrial dysfunction leads to the accumulation of oxygen free radicals and reduced ATP production from oxidative phosphorylation, reducing cell function and energy availability and leading to cell death [148,149].…”
Section: Meeting Energy Needs In Alsmentioning
confidence: 99%
“…Notably, in mutant SOD1-linked ALS functional defects in mitochondria can be observed early on, before symptoms are manifest (Tan et al, 2014). Several mechanisms, such as disruption of energy metabolism, impaired protein import machinery, and impaired calcium buffering, may contribute to mutant SOD1-mediated damage to mitochondria (Rothstein, 2009).…”
Section: Muscle Atrophymentioning
confidence: 99%